2020
DOI: 10.1016/j.amjoto.2020.102735
|View full text |Cite
|
Sign up to set email alerts
|

A survey of personal protective equipment use among US otolaryngologists during the COVID-19 pandemic

Abstract: Objective Describe current practices and challenges in personal protective equipment (PPE) use among US otolaryngologists during the COVID-19 pandemic. Study design Online survey. Setting Academic and non-academic healthcare institutions. Subjects and methods Subjects included US otolaryngology physicians. Emails were sent on April 17, 2020 to program coordinators at 121 residency programs, who were requested to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The authors describe the shortage of PPE as one of the reasons for the low adherence to PPE and our data confirm this speculation. The correlation between sufficient availability of PPE and high perceived level of safety is also reported for American ORLs [3,32] and was confirmed in this survey again.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The authors describe the shortage of PPE as one of the reasons for the low adherence to PPE and our data confirm this speculation. The correlation between sufficient availability of PPE and high perceived level of safety is also reported for American ORLs [3,32] and was confirmed in this survey again.…”
Section: Discussionsupporting
confidence: 81%
“…Among these HCW, due to the very nature of the specialty, otorhinolaryngologists (ORLs) have a high probability of exposure to patient aerosols [2,6,8,12,13,17,24,25]. Numerous recommendations for ORLs regarding the treat-ment of COVID-19 patients [1, 9-11, 19, 21, 22, 28] and protection against SARS-CoV-2 infection were published [4,5,14,18,20,27,31,32]. However, only a few studies are available reporting the number of infections or estimating the risk of infection for ORLs [15,23,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the need for using PPEs stands stronger than ever. PPEs should be adequately supplied while users must be well trained regarding their usage [3]. Medical supplies such as face shields, masks, mask adjusters, respirator parts, hands-free door openers, testing kits, nasopharyngeal swabs, quarantine booths and medical ventilators are considered vital for performing medical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a survey of 637 healthcare workers in Australia showed that while most understood the importance of using PPE, only a quarter felt like PPE supplies were always adequate [57] . However, PPE shortages were not present in all geographic or practice settings; US otolaryngologists reported “always” or “usually” having necessary PPE in a survey of residency programs [58] .…”
Section: Discussionmentioning
confidence: 99%